A Look at The Uzbek Instrument "Nay". (Zien Journal of Social Sciences and Humanities, 2021)
If you ask the name of a national instrument when talking with adolescents and young people who do not practice music today, unfortunately, many (almost all) cannot pronounce it correctly, let alone his voice, without even recognizing it. form. If we want to educate well-developed and open-minded young people, let's introduce them to our national instruments, let them understand the difference between them, the sound of each, let them touch, try to play, feel the relationship with the instrument. It is advisable to start this at an age when the knowledge gained is "carved in stone". If the above proposals are implemented, even if these children will not be musicians in the future, such feelings as our national instruments, their sound, their relationship with instruments, will remain in his psyche. When he sees our national instruments, he recalls the sweet memories of his childhood, he is proud, he does not forget our nationality anywhere in the world.